Bereavement, grief, and consolation: Emotional-affective geographies of loss during COVID-19. Issue 2 (July 2020) - Maddrell, Avril
COVID-19 has resulted in new global geographies of death ranging from cellular to global scales. These geographies are uneven, reflecting existing inequalities and failures of governance. In addition to death and bereavement, the pandemic has generated varied forms of loss and consolation, as well as negative and positive affective atmospheres, whereby emotions are mobilised and politicised. Understanding these emotional-affective topographies and 'emotional-viral-loads' is vital to wellbeing, resilience, and unfolding policy interventions locally and globally.